Los azteca-tepaneca: en torno a sus orígenes y gentilicio - Santamarina Novillo, Carlos (Revista Española de Antropología Americana, 2006)
This paper tries to meet the information available from the sources on the origins of the Tepanecs —one of the main Aztec peoples—, relating to other groups of the Mesoamerican central area according to linguistic and cultural criteria. The etymology of the term is discussed, as well as its glyphic representations in the sources.